The 90-90-90 ART targets: Progress of the Marindi Sub-County Hospital, Homa Bay County, Kenya - Onyango, Susan Atieno; ADAMU, VE; Okomo, G. O.; Oketch, F. A. (Orapuh Journal, 2020)
Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) is an epidemic that the world still grapples with. In 2014, The Joint United Nations Program on HIV/AIDS (UNAIDS) set fast-track targets for 2020 to accelerate HIV response to end the HIV/AIDS epidemic by 2030. Ending the AIDS epidemic will motivate the development and public health efforts, indicating what global solidarity, multi-sectoral partnerships, and evidence-based actions can be achieved. The ’ambitious’ targets state that by 2020, 90% of all people living with HIV will know their HIV status, 90% of all people with diagnosed HIV infection will receive sustained antiretroviral therapy, and 90% of all people receiving antiretroviral therapy will have viral load suppression. The purpose of this study was to assess the progress of the Marindi Sub-County Hospital towards achieving the 2020 United Nations’ AIDS ’ambitious’ 90-90-90 targets towards HIV testing, antiretroviral therapy, and viral load suppression. At the time of this review, 1,823 people receiving ART at the hospital have been tested, representing 73 percent of people who know their HIV status, giving the second 90 percent health outcome target a 100 percent score. The viral load suppression rate in the hospital was 93.3 percent. Marindi Sub-County Hospital has achieved the second and the third 90 but is yet to fully achieve the first 90. Achieving the second and third 90 may be right, but without achieving the first 90, it still means that many people who are HIV positive are not accessing treatment, which can lead to an increase in HIV-related morbidities, mortalities, and new HIV infections. Believably, the ’90–90–90 targets’ remain a powerful tool to assess progress towards HIV elimination and drive standards in care for PLHIV. From these results, 90-90-90 is not only feasible but also achievable.